Production of spherical ester wax powders by melt emulsification for Additive Manufacturing - Tischer, Florentin; Düsenberg, Björn; Peukert, Wolfgang; Schmidt, Jochen (Procedia CIRP, 2022)
Powder bed fusion of polymers with laser beam (PBF-LB/P) involves selectively melting plastic micro particles with a laser and building up the parts layer by layer, which offers great freedom of design. However, the choice of commercially available thermoplast feedstock powders is limited (90% polyamides). In order to extend the range of materials, this contribution presents the production of highly spherical micro particles by melt emulsification followed by spray agglomeration for ester wax. The effect of process parameters during emulsification (energy input, surfactant to polymer ratio) on the particle size distribution is demonstrated in detail for the ester wax system. In order to generate and tune particle sizes to a range suitable for PBF, melt emulsified ester wax dispersions are spray agglomerated. Agglomerated ester wax powders were used for the PBF process to manufacture tensile strength specimens type 5A.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Additive manufacturing; ester wax; Polycaprolactone; Melt emulsification; Polymers; Spray agglomeration